Simple shear of metal sheets at high rates of strain - Nguyen, H.V.; Nowacki, W.K. (Archives of Mechanics, 1997)
The test of dynamic (at high rates of strain) plane shear is discussed. Use is made of the new shear device in which the loading and displacements are controlled by the Split Hopkinson Pressure Bar acting in compression. This device allows to perform tests under the plane shear state in a specimen having the form of metal sheets. Simplified analytical solution of the boundary-value problem in the case of simple shear is prescribed. The analytical solution of the initial-boundary problem is compared with the experimental data.